Plastic relaxation and solute segregation to β-Nb second phase particles in Zr-Nb alloys: A discrete dislocation plasticity study. (November 2021) - Reali, Luca; Balint, Daniel S.; Sutton, Adrian P.; Wenman, Mark R.
Abstract: There is clear evidence in the literature that iron segregates to the interface of second phase particles (SPPs) in unirradiated Zr-Nb alloys, and that it does not do so in the presence of radiation damage. In this work, a discrete dislocation plasticity model is developed that takes into account the long-range stress field of the SPP interface. A simple analytical model is also outlined, providing an upper bound for estimating the amount of interstitial segregation. The model provides a possible mechanism to explain both the iron segregation to coherent SPPs and its subsequent loss after irradiation. Qualitatively, the model proved to be insensitive to variations of all geometrical and computational parameters, allowing for general conclusions to be drawn. The model suggests that the segregation originates from a tensile field of order 1 GPa induced by the dislocations generated during the plastic relaxation around the SPP. This leads to the six-fold increase in the iron concentration observed in experiments. In the model, the loss of SPP/matrix coherency after irradiation causes the dislocations to drift away from the interface, and the iron concentration is homogenised accordingly. The hydrogen concentration was also predicted and found to be about 50% higher than in the bulk zirconium matrix at room temperature. The computational framework is built to be fast, making possible a statistical analysis on over five hundred simulations for improved reliability of the predictions. Graphical abstract: Highlights: Mechanistic explanation of Fe segregation to second phase particles. Discrete dislocation plasticity model of the plastic relaxation around Nb particles. Prediction of H segregation to Nb particles with implications for hydride formation. Statistical analysis for improved robustness and reliability.